Language Development Barriers Encountered by Young Dual Language Learners as a Result of Early Exposure to Media: A Case Study (International Journal of Language, Literacy and Translation, 2025)
Benefits of bilingualism abound in the literature. However, some scholars claim that young children who are exposed to dual language through early media viewing at an early age may experience language development problems. Such problems may in turn have them undergo therapies which can be counterproductive to their developmental milestones, particularly their dual language development.  This research aims to gain deeper insights into the impact of early media viewing on young children’s early dual language acquisition. In this regard, a case study of five young dual language learners experiencing language development problems diagnosed as symptoms of Autistic Spectrum Disorder (ASD) and Mental Retardation (MR) was conducted. Specifically, in order to gain preliminary data about their language development problems, the participants’ parents were interviewed, and an estimated 108-hour language intervention sessions were observed. Upon having conducted 108-hour observation, the researcher did not identify any symptoms of pragmatic, affective and grammatical prosody which lead to participants’ context blindness and problem-solving disabilities as the main characteristics of ASD and MR.  Findings of this study revealed that early dual language exposure through media viewing without adequate social interaction may pertinently result in language development problems. It was also found that such problems are often misinterpreted as symptoms of ASD or of MR rather than the processes of bilingualism. It is therefore recommended that appropriate language intervention programs which provide adequate social interactions can really help young learners improve their dual language development.